2017
DOI: 10.1111/jop.12553
|View full text |Cite
|
Sign up to set email alerts
|

Oral squamous cell carcinoma in the background of oral submucous fibrosis is a distinct clinicopathological entity with better prognosis

Abstract: The OSCC-OSMF was found to be a clinicopathologically distinct entity with a better grade of tumor differentiation, less incidence of nodal metastases, and early detection (early clinical TNM stage) compared to OSCC. All these factors probably contribute to a better prognosis and increased 3-year disease-free survival in OSCC-OSMF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 25 publications
3
63
0
Order By: Relevance
“…As OSMF malignant transformation is known to be independent of stage and site in the affected oral cavity (Figure C), grouping OSMF patients with malignant transformation in late stages may result in losing vital data with prognostic value. Hence, the validity of any clinicopathological classification and its usefulness in treatment planning remains questionable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As OSMF malignant transformation is known to be independent of stage and site in the affected oral cavity (Figure C), grouping OSMF patients with malignant transformation in late stages may result in losing vital data with prognostic value. Hence, the validity of any clinicopathological classification and its usefulness in treatment planning remains questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, histopathological grading only has a role in understanding the progress of OSMF, but its usefulness in monitoring disease progression and overall treatment planning remains uncertain . Biopsy and histopathological grading are of course important in the diagnosis of suspected lesions …”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, the majority of patients with oral cancer habitually chew areca quid, which frequently induces oral submucous fibrosis and limitation of mouth opening . Studies have shown that OSCC associated with oral submucous fibrosis tends to have better treatment outcome and more favorable prognosis . Although severe oral submucous fibrosis was more frequently found in our mandibular lip‐split patients, it is not likely that the difference could have a negative impact on disease prognosis for this group of patients.…”
Section: Discussionmentioning
confidence: 73%
“…23 Studies have shown that OSCC associated with oral submucous fibrosis tends to have better treatment outcome and more favorable prognosis. 24,25 Although severe oral submucous fibrosis was more frequently found in our mandibular lipsplit patients, it is not likely that the difference could have a negative impact on disease prognosis for this group of patients. Another reason of restricted mouth opening in our patients was the reflex spasm of muscles induced by tumorassociated pain or infection, which has not been found to have an effect on the prognosis of oral cancers.…”
Section: Discussionmentioning
confidence: 82%
“…This model of carcinogenesis and microenvironment is highly specific and unique for OSF malignant transformation. Hence, oral squamous cell carcinoma (OSCC) in the background of OSF (OSCC‐SMF) has been proposed as a biologically and prognostically distinct entity . The identification of disease process in such a relationship would be immensely helpful to manage OSF cases at an early stage and prevent or identify the risk of malignant transformation.…”
Section: Introductionmentioning
confidence: 99%